The Liability Of User-Generated Content-Based Digital Service Platforms For Copyright Infringement Following Constitutional Court Decision No.84/PUU-XXI/2023 - Nur Amany Burhan (Utan Kayu Publishing, 2025)
The rapid advancement of information and communication technology has been accompanied by the increasing use of digital service platforms by various segments of society, facilitating the display and dissemination of creative works. However, this development has also led to the unauthorized use of copyrighted works by third parties. This study aims to analyze the responsibility of user-generated content (UGC)-based digital service platforms concerning copyright infringement, particularly in light of Constitutional Court Decision No. 84/PUU-XXI/2023, which broadens the interpretation of Article 10 of the Copyright Law regarding UGC-based platforms. This research employs a normative juridical method, focusing on the analysis of legal norms and their application. The findings reveal that Constitutional Court Decision No. 84/PUU-XXI/2023 affirms the heightened responsibility of digital platforms to proactively prevent copyright violations. Digital platforms are expected to implement preventive measures, including content filtering mechanisms, to minimize the risk of copyright infringement before publication